Sealing Effects on Organic Pore Development in Marine Shale Gas: New Insights from Macro- to Micro-Scale Analyses - Qiumei Zhou; Hao Xu; Wen Zhou; Xin Zhao; Ruiyin Liu; Ke Jiang (Energies)
The physics of how organic pores change under high thermal evolution conditions in overmature marine shale gas formations remains unclear. In this study, systematic analyses at the macro- to micro-scales were performed to reveal the effects of the sealing capacity on organic pore development. Pyrolysis experiments were conducted in semi-closed and open systems which provided solid evidence demonstrating the importance of the sealing capacity. Low-maturity marine shale samples from the Dalong Formation were used in the pyrolysis experiments, which were conducted at 350 °C, 400 °C, 450 °C, 500 °C, 550 °C, and 600 °C. The pore characteristics and geochemical parameters of the samples were examined after each thermal simulation stage. The results showed that the TOC of the semi-closed system decreased gradually, while the TOC of the open system decreased sharply at 350 °C and exhibited almost no change thereafter. The maximum porosity, specific surface area, and pore volume of the semi-closed system (10.35%, 2.99 m2/g, and 0.0153 cm3/g) were larger than those of the open system (3.87%, 1.97 m2/g, and 0.0059 cm3/g). In addition, when the temperature was 600 °C, the pore diameter distribution in the open system was 0.001–0.1 μm, while the pore diameter distribution in the semi-closed system was 0.001–10 μm. The pore volumes of the macropores and mesopores in the semi-closed system remained larger than those in the open system. The pore volumes of the micropores in the semi-closed and open systems were similar. The pyrolysis results indicated that (1) the pressure difference caused by the sealing capacity controls organic pore development; (2) organic pores developed in the semi-closed system, and the differences between the two systems mainly occurred in the overmature stage; and (3) the differences were caused by changes in the macropore and mesopore volumes, not the micropore volume. It was concluded that the sealing capacity is the key factor for gas pore generation in the overmature stage of marine shale gas reservoirs when the organic matter (OM) type, volume, and thermal evolution degree are all similar. The macropores and mesopores are easily affected by the sealing conditions, but the micropores are not. Finally, the pyrolysis simulation results were validated with the Longmaxi shale and Qiongzhusi shale properties. The Longmaxi shale is similar to semi-closed system, and the Qiongzhusi shale is similar to open system. Two thermal evolution patterns of organic pore development were proposed based on the pyrolysis results. This study provides new insights into the evolution patterns of organic pores in marine shale gas reservoirs.